An optimal design of the broadcast ephemeris for LEO navigation augmentation systems. Issue 1 (2nd January 2022) - Guo, Xueli; Wang, Lei; Fu, Wenju; Suo, Yingbo; Chen, Ruizhi; Sun, Hongxing
ABSTRACT: As the deployment of large Low Earth Orbiters (LEO) communication constellations, navigation from the LEO satellites becomes an emerging opportunity to enhance the existing satellite navigation systems. The LEO navigation augmentation (LEO-NA) systems require a centimeter to decimeter accuracy broadcast ephemeris to support high accuracy positioning applications. Thus, how to design the broadcast ephemeris becomes the key issue for the LEO-NA systems. In this paper, the temporal variation characteristics of the LEO orbit elements were analyzed via a spectrum analysis. A non-singular element set for orbit fitting was introduced to overcome the potential singularity problem of the LEO orbits. Based on the orbit characteristics, a few new parameters were introduced into the classical 16 parameter ephemeris set to improve the LEO orbit fitting accuracy. In order to identify the optimal parameter set, different parameter sets were tested and compared and the 21 parameters data set was recommended to make an optimal balance between the orbit accuracy and the bandwidth requirements. Considering the real-time broadcast ephemeris generation procedure, the performance of the LEO ephemeris based on the predicted orbit is also investigated. The performance of the proposed ephemeris set was evaluated with four in-orbit LEO satellites and the results indicate the proposed 21 parameter schemes improve the fitting accuracy by 87.4% subject to the 16 parameters scheme. The accuracy for the predicted LEO ephemeris is strongly dependent on the orbit altitude. For these LEO satellites operating higher than 500 km, 10 cm signal-in-space ranging error (SISRE) is achievable for over 20 min prediction.